PERLINDUNGAN HUKUM HAK CIPTA ATAS KARYA TULIS YANG DITERBITKAN MELALUI MEDIA ELEKTRONIK (Faculty of Law, University of Palembang, 2023)
A form of copyright legal protection for electronic media is that the author can repressively prosecute individuals involved in the written work. Preventatively, writers who publish written works via electronic media also receive legal protection from the government which aims to prevent violations before they occur. Then, the legal consequences if there is a violation of a written work through electronic media, namely, in a repressive manner, a person who violates a copyrighted work, in this case a written work, will receive sanctions in the form of fines, imprisonment and additional penalties given by the government if the author is the one who disadvantaged by prosecution. In Constitution No. 28 of 2014 concerning Copyright, it is also explained that